2011 FEBRUARY 15 CME IN THE INTERPLANETARY MEDIUM BY OBSERVATIONS OF RADIO SOURCE SCINTILLATIONS AT THE DECAMETER WAVELENGTHS - Kalinichenko, N. N.; Konovalenko, O. O.; Brazhenko, A. I.; Solov’ev, V. V. (Видавничий дім «Академперіодика», 2013)
The high efficiency of the interplanetary scintillation methodat the decameter wavelengths for detection of coronal mass ejectionsbeyond Earth’s orbit is shown. It is established that coronalmass ejection in the interplanetary medium continuesslowing at distances from 1 to 1.7 AU from the Sun, its velocitytending to that of the ambient solar wind, the angular size beingno less than 66°.